Women’s language analysis used by female characters in mulan movie - Anggreani, Sarah; Anggraeni, Diana; Wulansari, Dini (International Journal of Curriculum Development, Teaching and Learning Innovation, 2024)
Women’s language and its features have been a subject of linguistic study for decades. This research explores the women's language features used by female characters in the 2020 movie "Mulan," directed by Niki Caro. Utilizing Robin Lakoff's (1975) framework of women's language features and Judy Pearson's (1985) theory on the functions of these features. The purposes of this study are to identify the specific women's language features in the Mulan movie and to examine the functions of women's language features. The study employs a descriptive qualitative method, analyzing the film's script and dialogues to extract relevant data. The results indicate that there are 8 women's language features which are hedges and fillers, intensifiers, tag questions, super polite forms, emphatic stress, empty adjectives, hypercorrect grammar and rising intonation on decralative. The functional analysis revealed 5 functions of women's language features which are expressing uncertainty, getting responses, softening utterances, initiating discussions, and expressing feelings and opinions. This study contributes to the understanding of women's language in contemporary media, highlighting how female characters in "Mulan" use specific linguistic features to navigate their interactions and express themselves